A super-sensitive auxin-inducible degron system with an engineered auxin-TIR1 pair. Issue 18 (17th September 2020) - Nishimura, Kohei; Yamada, Ryotaro; Hagihara, Shinya; Iwasaki, Rie; Uchida, Naoyuki; Kamura, Takumi; Takahashi, Koji; Torii, Keiko U; Fukagawa, Tatsuo
Abstract: The auxin-inducible degron (AID) system enables rapid depletion of target proteins within the cell by applying the natural auxin IAA. The AID system is useful for investigating the physiological functions of essential proteins; however, this system generally requires high dose of auxin to achieve effective depletion in vertebrate cells. Here, we describe a super-sensitive AID system that incorporates the synthetic auxin derivative 5-Ad-IAA and its high-affinity-binding partner OsTIR1 F74A . The super-sensitive AID system enabled more than a 1000-fold reduction of the AID inducer concentrations in chicken DT40 cells. To apply this system to various mammalian cell lines including cancer cells containing multiple sets of chromosomes, we utilized a single-step method where CRISPR/Cas9-based gene knockout is combined with insertion of a pAID plasmid. The single-step method coupled with the super-sensitive AID system enables us to easily and rapidly generate AID-based conditional knockout cells in a wide range of vertebrate cell lines. Our improved method that incorporates the super-sensitive AID system and the single-step method provides a powerful tool for elucidating the roles of essential genes.